I{EFOIWASI DAN REORIENTASI PENDIDIKAN DI·LEMBAGA PENDIDIKAN ISLAM - Jailani Jailani (Jurnal Cakrawala Pendidikan, 2000)
'rhe nUldrasah as a subsystenlin the nationalcducatiollulsysteJn has heen facing arious problenls,S()I1IC rl'sulting fnull such an external cause asglohalizatioll and SOUle others froln such internalcausesas lilnitations of human resources and theratificationof Law No. 22 of 1999. Among the effortstosolve the prOOlCI11S are refonnation and reorientationof the educational system in theinstitution.Someof the reformation involves the policiestakenby the institution in matters such as decisions onfuture fornlats and options·in affiliations with· theDepartmentof National Education or the Departmentof Religion with the various consequences andimplications (including equalityofoutput with that ofpublic schools). Other efforts take the form ofilnprovenlents of human resources through variousbreakthroughs), the establishmentof model madrasahsand integrated madrasahs,etc. The reorientation oftheIslamic education at themadrnsahis' done amongothers by making reorderingsin its "mission, vision,and function and through diversificationsof. itsdepartments and course programs (formerlydominatc'dby course programs on religion, . nowconsisting alsoof course programs on generalsubjects, skills, 'and vocations) while still retaining itsspecific characteristics.Jt is hoped that these efforts can be the earlysolutionsin responding to the challenges of the futureittHI fhtt tthtt ntiutH1J iit~fiHUiou tUIl pIny fl hlgger paUin the preparation of human resources possessingcOlnpctitive competence and added values - masteryofscience and technology and possession ofcOlnnlendable morals.